2002
DOI: 10.1007/s00203-002-0409-3
|View full text |Cite
|
Sign up to set email alerts
|

Tetrachloroethene reductive dehalogenase of Dehalospirillum multivorans : substrate specificity of the native enzyme and its corrinoid cofactor

Abstract: The substrate specificity of the tetrachloroethene reductive dehalogenase of Dehalospirillum multivoransand its corrinoid cofactor were studied. Besides reduced methyl viologen, titanium(III) citrate could serve as electron donor for reductive dehalogenation of tetrachloroethene (PCE) and trichloroethene to cis-1,2-dichloroethene. In addition to chlorinated ethenes, chlorinated propenes were reductively dechlorinated solely by the native enzyme. trans-1,3-Dichloropropene, 1,1,3-trichloropropene and 2,3-dichlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 0 publications
7
70
1
Order By: Relevance
“…Cultivation of Dehalobacter restrictus depends on the presence of cobalamin in the medium (14), and growth on cobinamide-containing medium ceased after a few transfers (data not shown). All these results indicated that the corrinoid present in PCE-RDase is a cobalamin, which is in contrast to the recent findings obtained with Dehalospirillum multivorans; for the latter organism it has been shown that the corrinoid isolated from the PCE-RDase had different catalytic dechlorination properties than commercially available cobalamin (24). The cobalamin content determined spectrophotometrically by measuring the difference between A 580 and A 640 was 0.97 Ϯ 0.07 mol of cobalamin/mol of enzyme (Fig.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Cultivation of Dehalobacter restrictus depends on the presence of cobalamin in the medium (14), and growth on cobinamide-containing medium ceased after a few transfers (data not shown). All these results indicated that the corrinoid present in PCE-RDase is a cobalamin, which is in contrast to the recent findings obtained with Dehalospirillum multivorans; for the latter organism it has been shown that the corrinoid isolated from the PCE-RDase had different catalytic dechlorination properties than commercially available cobalamin (24). The cobalamin content determined spectrophotometrically by measuring the difference between A 580 and A 640 was 0.97 Ϯ 0.07 mol of cobalamin/mol of enzyme (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…Similar experiments with PCE-RDase of Dehalobacter restrictus and increasing amounts of the D˙donor d 7 -isopropyl alcohol providing evidence for a radical mechanism with free cobalamin did not indicate that a dissociative one-electron transfer is involved in the cobalamin enzyme-catalyzed reaction (data not shown). The dechlorination of trans-1,3-dichloropropene to a mixture of trans-1-chloropropene, cis-1-chloropropene, and 3-chloropropene by the PCE-RDases of Dehalospirillum multivorans and Desulfitobacterium hafniense strain PCE-S, on the other hand, is in accordance with a dechlorination mechanism involving a radical intermediate (24). Rapid freezing experiments combined with EPR analysis might provide additional indications of the reaction mechanism involved.…”
Section: Resultsmentioning
confidence: 86%
“…Propyl iodide (50 M) completely inhibited dechlorination in the dark; the inhibition could be reversed by illumination. These findings provide strong evidence for the involvement of a corrinoid in the dichloroelimination reaction (19,20). In vivo studies with three different 2,3-DCB stereoisomers as electron acceptors were performed (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…The positions of the respective excised protein bands were determined by the method as described by Adrian et al (2007). Gel fragments were used for in-gel activity assays and the dechlorination activity of PCE was conducted as previously described (Neumann et al, 2007). The protein band identified to show dechlorination activity was eluted and concentrated for a second gel electrophoresis step (Adrian et al, 2007).…”
Section: Genome Walking Of the Rdase Genesmentioning
confidence: 99%